Physiological and behavioral parameters of pain and stress in mares during and after transvaginal ultrasound-guided follicular aspiration - Van den Branden, Emma; Salamone, Matthieu; Broothaers, Klaartje; Peere, Sofie; Polfliet, Ellen; Dewulf, Manon; Van Steenkiste, Glenn; van Loon, Gunther; Smits, Katrien; Govaere, Jan (Frontiers in Veterinary Science, 2025)
IntroductionThe use of transvaginal ultrasound-guided follicle aspiration (TVA) for oocyte collection has become a widely used procedure in horses for in vitro embryo production (IVEP). The TVA procedure is characterized by various manipulations, which are physical restraint, perineal preparation, transrectal palpation, insertion of an intravaginal device, and needle punctures. These repeated transvaginal and transovarian punctures have raised concerns about their potential effects on mare welfare. Our study aimed to investigate the effects of TVA manipulations, and especially puncturing, on pain and stress in mares in a commercial set-up.MethodsTherefore, eight mares were subjected to three TVA procedures: two with puncturing (P+) and one without (P−, control). Before, during and after all TVA procedures, blood was collected for serum glucose, lactate and cortisol levels, and facial pain scores were assessed. An electrocardiogram (ECG) was recorded for each mare before and during the procedure to measure heart rate (HR) and heart rate variability (HRV). Parameters in response to manipulations and puncturing were analyzed using linear mixed effect models for each outcome variable at different timepoints during the procedure.ResultsResults revealed that puncturing during TVA did not significantly influence serum metabolite levels, facial pain scores, HR, or HRV over the complete procedure (p > 0.05). Notably, HR did not increase at the moment of puncturing (p > 0.05), and no significant changes in HRV parameters between P+ and P− were detected (p > 0.05). Both P+ and P− procedures triggered significant increases in cortisol and lactate levels, facial pain scores, and HR during restraint in stocks and perineal preparation compared to the day before and the day after TVA (p < 0.05). Interestingly, even without puncturing, manipulations in the P− procedure were sufficient to induce significant elevations in metabolite levels and facial pain scores compared to the day before and after (p < 0.05).DiscussionThese results indicate that the TVA procedure induces stress responses in mares, predominantly associated with all manipulations specific to TVA, while the effect of puncturing itself was minimal. All effects were acute, with parameters returning to baseline when measured 24 h later.